The Influence of E-Samsat Program, Mobile Samsat, Taxpayer Satisfaction and Tax Socialization on Motor Vehicle Taxpayer Compliance - Wibowo, Ferry Setyo; Whetyningtyas, Aprilia; Handayani, Retno Tri (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research aims to identify the effect of e-Samsat, mobile Samsat programs, taxpayer satisfaction and tax socialization on motor vehicle taxpayer compliance. The theory used in research is the Theory of Planned Behavior and the Technology Acceptance Model theory. This research was attempted at the Grobogan SAMSAT Office with a total population of 532,303 taxpayers. The size of the illustrations is calculated using the slovin formula so that 406 illustrations in 2021 must be taxed. The procedure for determining illustrations uses accidental sampling. Collecting information in this study using primary data. Distribution of questionnaires and information analysis method used is a multiple linear regression analysis. The research results show that the e-samsat, mobile samsat and mandatory satisfaction programs have a positive effect on motor vehicle tax compliance while tax socialization has no effect on motor vehicle tax compliance.